1987
DOI: 10.1148/radiology.162.1.3538148
|View full text |Cite
|
Sign up to set email alerts
|

Deep venous thrombosis: US assessment using vein compression.

Abstract: To assess vein compressibility as a simple ultrasound (US) technique to determine the presence of venous thrombi, 51 patients undergoing contrast material venography of the lower extremity because of a clinical suspicion of deep venous thrombosis (DVT) also underwent high-resolution US evaluation of the veins. DVT was diagnosed on 28 venograms. In 25 patients US studies demonstrated non-compressibility of the veins, indicating the presence of clot. In 23 patients with normal venograms, US examinations demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
1
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(73 citation statements)
references
References 0 publications
0
70
1
2
Order By: Relevance
“…Although the use of Doppler ultrasonography to detect DVT may not be the gold standard compared to venography, it is noninvasive and provides good sensitivity (89%) and specificity (100%) in detecting proximal DVT. (20) In addition, we had a moderately large number of patients and gathered valuable data on the incidence of DVT in cemented and uncemented hemiarthroplasty for traumatic displaced femoral neck fractures in an Asian population. We also attempted to eliminate potential confounders by using multiple logistic regression analysis models.…”
Section: Discussionmentioning
confidence: 99%
“…Although the use of Doppler ultrasonography to detect DVT may not be the gold standard compared to venography, it is noninvasive and provides good sensitivity (89%) and specificity (100%) in detecting proximal DVT. (20) In addition, we had a moderately large number of patients and gathered valuable data on the incidence of DVT in cemented and uncemented hemiarthroplasty for traumatic displaced femoral neck fractures in an Asian population. We also attempted to eliminate potential confounders by using multiple logistic regression analysis models.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in symptomatic patients have consistently shown a high sensitivity and specificity (97% and 97%) for proximal deep venous thrombosis. [17][18][19] Conventional duplex imaging, however, has its drawbacks. Errors continue to be made in the detection of thrombi located in the calf veins and femoral adductor canal region.…”
Section: Discussionmentioning
confidence: 99%
“…Doppler ultrasound is currently the most common technique for the diagnosis of symptomatic DVT. B-mode ultrasonography allows a bi-dimensional image of the vessels of the lower extremity and when compression techniques are used, a sensitivity of up to 90% and a specificity of 96% to 100% can be achieved in the detection of DVT (Cronan et al, 1987;O'Leary et al, 1988).…”
Section: Imaging In Dvtmentioning
confidence: 99%
“…When color Doppler flow is used with compression Bmode ultrasonography (color duplex ultrasonography), additional data on the direction of flow is gained (Cronan et al, 1987;O'Leary et al, 1988).…”
Section: Imaging In Dvtmentioning
confidence: 99%